Estudo teórico: UPQC-UPS monofásica com possibilidade de filtragem ativa utilizando a teoria p-q - Pereira, Dante Victor Shimoda (2013)
This work proposes the design of an UPQC-UPS high efficiency single phase 1.4 kVA with active filter capabilities throughout the parallel and series converters. With this topology, it is possible to obtain high efficiency and combine the advantages of both on-line and line interactive UPS systems improving, at the same time, the grid energy quality. The series/parallel compensation references were generated using the p-q Theory which defines a joint of power definitions to deal with electric systems under non-sinusoidal conditions. According to the simulation results, it was shown that the system input current has a low total harmonic distortion (THDi) and it presents high power factor. Also, the load voltage has a sinusoidal shape with low total harmonic distortion (THDv), both in its grid and battery mode operation. Such simulations were developed in the software PSCAD/EMTDC.